Book Tax Different, Kepemilikan Keluarga dan Persistensi Laba pada Perusahaan Go-Public Indonesia - Yusri Yusri; Chairina Chairina; Subambang Harsono (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2022)
The aims of this study are to examine the factors affecting book-tax difference (BTD) and analyze the influence of BTD and family ownership to earning persistence. This research use panel data with population of listed company in Indonesia Stock Exchange. The result shows significant correlation for all factors affecting BTD to BTD. Earning persistence test shows that both different value and/or sources in BTD give different implications to earning persistence. This research also find evidence that family ownership significantly influence the persistence of earning exclude when the value of BTD is large negative-coming from earning management and tax avoidance activity.